CeIII-promoted oxidation: Efficient aerobic one-pot eco-friendly synthesis of oxidized bis(indol-3-yl)methanes and cyclic tetra(indolyl)dimethanes - Silveira, Claudio C. (2012)
Indoles and benzaldehyde derivatives undergo an efficient one-pot smooth condensation and a further atmospheric-pressure aerobic dehydrogenation with CeCl3 in i-PrOH, to afford the corresponding oxidized bis(indol-3-yl)methanes. Use of 2,2-bisindole as the heterocyclic precursor provides cyclic tetra(indolyl)dimethane derivatives, which further undergo partial oxidation to the related calix-shaped macrocycles, carrying an all cis 1,3,7-cyclodecatriene core and supporting a 2,2-biindolylidene moiety. The syntheses of these high value-added compounds is operationally simple and can be performed at room temperature under mild, neutral and environmentally friendly conditions.